Identifikasi Lagu Berdasarkan Lirik Menggunakan Algoritma Boyer-Moore - Apriana, I Komang Gede; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023, 2023)
Many people want a fast and efficient search method as technology advances. A song search is one example of this kind of search. A song is a collection of sing-along lyrics with rhythms and melodies for many to enjoy. Due to the large number of song lovers, some people are often constrained by the title of the song to be sung. This is caused by one factor, namely only memorizing some of the lyrics of the song to be sung. Given these problems, in this study a solution was developed, namely the application of identifying song titles based on input from the user's lyrics. The algorithm used by researchers in this study is the Boyer-Moore Algorithm, which is considered better in terms of matching substrings in longer texts. The research method used includes literature study, data collection, implementation, and testing. The implementation results show that the system successfully recognizes song titles with high accuracy based on the given piece of lyrics. In conclusion, this study proves that the development of a song title identification system based on snippets of lyrics using the website-based Boyer-Moore algorithm is an effective method. This system can help users recognize song titles based on the snippets of lyrics they remember with high accuracy.